Prevent Dengue Hemorrhagic Fever with the Implementation of Clean and Healthy Living Behavior in Elementary Schools in SDN Sukamanah II 2022 - Hana Fitria Andayani; Dalla Zahira Khoiriyah; Nadya Nur Afifah; Rizal Ramdani; Safirah Hayya Firgin; Syifa Gania Auliya (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
Dengue hemorrhagic fever (DHF) is a disease caused by dengue viruses, which are spread by Aedes aegypti and Aedes albopictus mosquito bites.DHF is most common in unconcerned residential areas with poor environmental sanitation. This can be attributed to the community's lack of knowledge and application of clean and healthy live behaviors (CHLB). Purpose: To increase knowledge and change the habitual behaviors of children in SDN Sukamanah II to avoid the DHF virus by doing clean and healthy live behavior. Method: Lecture, discussion, and giving a pre-and post-test.Result: The average children at SDN Sukamanah II do not know about the transmission, causes, symptoms, dangers, and prevention of DHF by implementing clean and healthy live behavior in schools. So it can be concluded that our community service activities at SDN Sukamanah II are successful because there is an increase in knowledge among the respondents.